Financial frictions and global spillovers - Norbert Metiu; Björn Hilberg; Michael Grill (Deutsche Bundesbank, 2015)
We investigate whether frictions in US financial markets amplify the international propagation of US financial shocks. The dynamics of the US economy is modeled jointly with global macroeconomic and financial variables using a threshold vector autoregression that allows us to capture regime-dependent dynamics conditional on the tightness of US credit market conditions, measured by the excess bond premium on US corporate bonds. The US economy switches from a regime of unconstrained access to credit to one characterized by tight credit whenever the bond risk premium exceeds a critical threshold. US financial shocks have an insignificant effect on the global economy when borrowers have unconstrained access to credit. On the contrary, US financial shocks give rise to a worldwide economic contraction in the tight credit regime. Moreover, US financial shocks are a relatively more important driver of US and global business cycles in times of tight credit.
Keywords: C32; C34; E32; G01; F44; 330; Financial frictions; Financial shocks; Nonlinear dynamics; Spillover